Procuring Firm Growth: The Effects of Government Purchases on Firm Dynamics - Claudio A. Ferraz do Amaral; Frederico S. Finan; Dimitri Szerman (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2015)
This paper tests whether demand shocks affect firm dynamics. We examine whetherfirms that win government procurement contracts grow more compared to firms thatcompete for these contracts but do not win. We assemble a comprehensive data setcombining matched employer-employee data for the universe of formal firms in Brazilwith the universe of federal government procurement contracts over the period of2004 to 2010. Exploiting a quasi-experimental design, we find that winning at leastone contract in a given quarter increases firm growth by 2.2 percentage points overthat quarter, with 93% of the new hires coming from either unemployment or the informalsector. These effects also persist well beyond the length of the contracts. Partof this persistence comes from firms participating and wining more future auctions, aswell as penetrating other markets
Keywords: 330; Demand Shocks; Firm Productivity; Public Procurement